Scandinavian perspectives on life support at the border of viability - Janicke Syltern; Janicke Syltern (Frontiers Media S.A., 2024)
Advances in neonatal medicine have allowed us to rescue extremely preterm infants. However, both long-term vulnerability and the burden of treatment in the neonatal period increase with decreasing gestational age. This raises questions about the justification of life support when a baby is born at the border of viability, and has led to a so-called "grey zone", where many professionals are unsure whether provision of life support is in the child's best interest. Despite cultural, political and economic similarities, the Scandinavian countries differ in their approach to periviable infants, as seen in their respective national guidelines and practices. In Sweden, guidelines and practice are more rescue-focused at the lower end of the border of viability, Danish guidelines emphasizes the need to involve parental views in the decision-making process, whereas Norway appears to be somewhere in between. In this paper, I will give an overview of national consensus documents and practices in Norway, Sweden and Denmark, and reflect on the ethical justification for the different approaches.